KEBUGARAN KARDIORESPIRASI PEMAIN UKM SEPAKBOLA UNIVERSITAS MUHAMMADIYAH PURWOKERTO 2015 - Febrianta, Yudha (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2016)
This study aims to determine the cardiorespiratory fitness of football players of students Activity Unit of University of Muhammadiyah PURWOKERTO. This research is a quantitative descriptive. The population in this study are all of football players of Students Activity Unit of University of Muhammadiyah Purwokerto, with the number of 20 persons (respondents). The instruments in this study was by Multi Stage Running tests with the reliability and validity of 0.9 by 0.6. Data were analyzed by descriptive with percentage, as well as by six categories: privileged, very good, good, average, less, and very less. From the results of research and discussion, it can be concluded that the level of cardiorespiratory fitness football player of students Activity Unit of University of Muhammadiyah Purwokerto was in privileged category of total 0 respondent (00,00%), 0 respondent (00,00%), in less category, 3 people ( 15.00%) in average. 2 persons (10,00) in good category, 2 people or (10.00%) in very good category, and 13 people or (65.00%) in privileged category